Late Eocene slab retreat, extension, and mantle upwelling inferred from mantle signatures in potassium-rich magmatism in NE Iran. Issue 9 (15th May 2023) - Alizadeh, Elahe; Li, Huan; Babazadeh, Shahrouz; Ma, Changqian; Förster, Michael W.
ABSTRACT: There is considerable debate regarding the petrogenesis of K-rich magma, which are believed to occur in subduction settings. The districts of the potassic rocks in the rear-arc of the Cenozoic Iran have not been thoroughly investigated. In this study, we investigate Late Eocene K-rich rocks of the Roshtkhar area of NE Iran. We employ whole-rock geochemistry, Sr-Nd-Hf-isotopes and zircon U-Pb age data of intrusive rocks to identify the mantle signature, evaluate the timing of emplacement, and determine the geodynamic setting. The Roshtkhar intrusive rocks (RIR) encompass a narrow compositional spectrum from syenite to monzonite, belonging to K-rich series, and are enriched in light rare earth elements and large ion lithophile elements such as Cs, Rb, Ba, Th, and U, with positive K, Pb, and Sr anomalies. U-Pb LA-ICP-MS dating of zircon from two samples yielded ages of ca. 38 Ma. Epsilon Hf values for investigated Eocene zircons display a variable range from +0.3 to +6.5. The RIR show relatively homogeneous initial epsilon Nd values ranging from +0.64 to −1.31 and modest variation in initial 87 Sr/ 86 Sr from 0.7048 to 0.7052. The data show mantle contribution with small involvement of Cadomian upper crustal material of up to 12% and an approximately 3% contribution fluid derived from subducted sediment into the mantle source. The lack of rocks that are purely derived from the lower crust in the study area further argues against the partial melting of lower crust that delaminated into the mantle. We suggest slab retreat, extension, and mantle upwelling as the main mechanisms for the generation of the primitive melts of RIR. Accordingly, decompression melting of metasomatized lithospheric mantle (e.g. phlogopite, apatite, and/or pargasite-bearing lherzolite) would be a plausible mechanism for the forming of K-rich basic melt in the mantle source.